2023
DOI: 10.3390/healthcare11212886
|View full text |Cite
|
Sign up to set email alerts
|

Functional Neuromyofascial Activity: Interprofessional Assessment to Inform Person-Centered Participative Care—An Osteopathic Perspective

Francesca Baroni,
Robert Schleip,
Lorenzo Arcuri
et al.

Abstract: Introduction: Health professionals and bodyworkers may be pivotal in promoting prevention programs, providing tailored advice and guidance to patients’ adherence to self-care strategies, such as physical activity. Contemporary evidence encourages manual therapists to involve patients in decision-making and treatment procedures integrating passive and active approaches in treatment planning. This manuscript provides a definition and applications of neuromyofascial movement patterns, discusses the significance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
(173 reference statements)
0
0
0
Order By: Relevance
“…Accumulating evidence from dissection studies confirms the role played by the myofascial meridians identified by Myers [26], which connect distant parts of the body via muscles and fascial tissues [29,30]. This anatomical and functional knowledge suggests that physical exercise should be framed as a whole-body rather than a local approach to have a faster, more balanced, and effective result [31].…”
Section: Introductionmentioning
confidence: 65%
“…Accumulating evidence from dissection studies confirms the role played by the myofascial meridians identified by Myers [26], which connect distant parts of the body via muscles and fascial tissues [29,30]. This anatomical and functional knowledge suggests that physical exercise should be framed as a whole-body rather than a local approach to have a faster, more balanced, and effective result [31].…”
Section: Introductionmentioning
confidence: 65%
“…This approach aims to increase awareness of how the body functions, behaves and interacts with others. With this knowledge inherited from early practitioners and renewed today, osteopathic practitioners have recently proposed additional treatment strategies administered not with patients lying on the table receiving passive manual therapy, but while performing functional movements [ 71 ]. The rationale is that hands-on experiential bodywork influences self-tracking of the lived body through body awareness.…”
Section: Discussionmentioning
confidence: 99%
“…The patient, being aware of the different reasoning that can be applied, makes sense of precedent treatments and shares with the osteopathic practitioner the decisions regarding the proposed osteopathic treatment planning. The progressive sequence of the overall physiotherapeutic and psychotherapeutic treatment plan is centered on the clinical context, based on available guidelines [ 95 ], and is indicated by the circled numbers 1 and 2; the subsequent personalized osteopathic treatment plan defined by shared decision-making [ 41 , 51 ] to promote participative-active osteopathic treatment [ 71 , 87 ] with a combination of touch-based and mindfulness-oriented strategies [ 97 , 98 , 99 ] and synchronized music listening [ 100 ], as well as self-management counseling [ 101 ] and is marked by the numbers 3 and 4. Abbreviations: symptom-oriented physical examination (SPE), functional physical examination (FPE), familial symptoms (FS), osteopathic palpatory findings (OPF), structure-function test (SFCT), manual assessment tests of central sensitization (CS), two-point discrimination test (TPD), and Waddell’s sign (WS).…”
Section: Figurementioning
confidence: 99%